Integration of functional complex oxide nanomaterials on silicon - Vila-Fungueiriño, José M.; Bachelet, Romain; Saint-Girons, Guillaume; Gendry, Michel; Gich, Marti; Gazquez, Jaume; Ferain, Etienne; Rivadulla, Francisco; Rodriguez-Carvajal, Juan; Mestres, Narcis; Carretero-Genevrier, Adrián (Frontiers in Physics, 2015)
The combination of standard wafer-scale semiconductor processing with the properties of functional oxides opens up to innovative and more efficient devices with high value applications that can be produced at large scale. This review uncovers the main strategies that are successfully used to monolithically integrate functional complex oxide thin films and nanostructures on silicon: the chemical solution deposition approach (CSD) and the advanced physical vapor deposition techniques such as oxide molecular beam epitaxy (MBE). Special emphasis will be placed on complex oxide nanostructures epitaxially grown on silicon using the combination of CSD and MBE. Several examples will be exposed, with a particular stress on the control of interfaces and crystallization mechanisms on epitaxial perovskite oxide thin films, nanostructured quartz thin films, and octahedral molecular sieve nanowires. This review enlightens on the potential of complex oxide nanostructures and the combination of both chemical and physical elaboration techniques for novel oxide-based integrated devices.